355 Comparison of Outcomes in Surgical and Endoscopic Transgastric Cystgastrostomy for Severe Acute Pancreatitis. (19th August 2022) - Mountjoy, P; Latif, J; Bandlamudi, N; Austin, A; Bhatti, I; Awan, A
Abstract: Aim: The heterogeneous nature of severe acute pancreatitis (SAP) renders decisions related to complications challenging. A select group of patients may be suitable for surgical (S-CG), which can be performed open or laparoscopic, or endoscopic (E-CG) transgastric cystgastrostomy (TCG) of symptomatic or infected retrogastric pancreatic collections (walled-off pancreatic necrosis (WOPN) or pseudocyst). There is limited data comparing outcomes between these approaches. Method: Retrospective analysis of all patients that underwent S-CG or E-CG was performed from a single, high-volume benign pancreatic centre between 2012 – 2021 inclusive. Patient demographics, clinical characteristics, and outcomes of these 3 groups was compared. One-way analysis of variance tests was used to compare categorical data. Results: 47 patients underwent TCG: 20 S-CG (12 open and 8 laparoscopic), and 27 E-CG. There was no statistical difference between S-CG and E-CG for age, body mass index (BMI), aetiology, organ failure and type or position of collection. S-CG patients had less burden of pre-existing co-morbidities (APACHE-II and Charlson-Co-morbidity-Index (CCI)) (p<0.05). S-CG patients had shorter length of stay, emergency readmission and reintervention (p<0.05). Those who underwent E-CG had higher burden of intervention due to persistent/recurrent pancreatic collections, with 33% mortality rate (p <0.05). Conclusions: S-CG, in a select group of patients, provides a single-staged intervention for drainage of transgastric pancreatic collections, especially when they predominantly contain solid necrosis and patient is suitable for general anaesthetic. Outcomes are favourable for S-CG, but multidisciplinary approach is critical to delineate the most appropriate approach for each individual patient.